Power minimization of WBSN using adaptive routing protocoL - Ammar Sabeeh Hmoud Altamimi; Omar Raad K. Al-Dulaimi; Amar A. Mahawish; M. M. Hashim; Mustafa S. T. (Institute of Advanced Engineering and Science, 2020)
The present work was an attempt to address a challenge of energy utilization or consumption in WBSN, it used a proposed routing algorithm based on ant optimization technique to distribute energy utilization efficiently on nodes. Thus reducing consumed energy and extending the life cycle of nodes, as well as avoiding damages might be occurred in tissues of patient`s body. At the beginning the proposed protocol was compared with conventional routing protocol LEACH to prove it`s efficiency in the extending of the life cycle of node, then it was used with experimental network was employed to examine energy utilizations. The obtained results were compared with others attained by conventional and developed routing protocols, there was considerable minimizing in the energy consumption that proved efficiency of proposed algorithm.